LEVELS OF CATHEPSIN-D AND NESTIN IN BREAST CANCER PATIENTS - Bahram Arif, Khalid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Breast cancer is the second most frequently cause of cancer deaths among women, therefore, new screening modalities could provide an extraordinary progress in understanding the mechanism of disease. In last decade, the role of Cathepsin-D (Cath-D) and Nestin which recently received attention as tumor markers, are remain unclear. Aim: Measurement the levels of Cath-D and Nestin in breast cancer patients (BCPs) and estimating an association of each marker to stage of disease, early and advanced, and to age of study patients. Materials and methods: An overall 48 adult women who attended to the Kirkuk Oncology Center (Kirkuk province, Iraq) and diagnosed clinically as BCPs; 24 at early stage and 24 at advanced stage, were selected to the present study that carried out from December (2022) to June (2023). The obtained sera were tested by specific ELISA kits.